Traffic and livability in Pretoria: exploring the impacts of traffic volume on the quality of street life in Pretoria - Tswai, Klass (My University, 2022)
Quality of life in cities and towns is of increasing concern to the public and to policymakers. One of the major threats to quality of life is the growing traffic volume in most cities. This research report assessed the impacts of traffic volume on the quality of street life or liveability in Pretoria by applying an existing research study of Donald Appleyard’s (1981) which was based in a residential neighbourhood in united states of America, in San Francisco, liveable streets. Like the original study, it compared responses of residents and other street users on streets with heavy, moderate and light traffic volumes and measured the effects on four liveability indicators including social interaction, stress, traffic hazard, and privacy and home territory. The results confirm that Appleyard’s findings that all four liveability indicators correlate inversely with traffic volume in San Francisco are applicable in South African context in the CBD of Pretoria, but furthermore this research also revealed strongly that there are other variable other than traffic volume influencing liveability in Pretoria including crime, economic activities and human-centred street design. It revealed that a heavy traffic street are dangerous, noisy and its effects on neighbouring and sense of possession of the street were apparently devastating. Whereas street with less or light traffic volume had more engaged residents, with had a sense of responsibility over their street, claimed the street as their own territory, they felt safer and residents had more friends and acquaintances.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Development Planning to faculty of Engineering and Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2021